How and When Health-Promoting Leadership Facilitates Employee Health Status: The Critical Role of Healthy Climate and Work Unit Structure - Liu, Shuang; Song, Zhimin; Xiao, Jincen; Chen, Peimin (Frontiers in Psychology, 2021)
Health-promoting leadership has attracted a lot of attention from scholars in recent years. However, majority studies focused on theoretical arguments rather than empirical examination. Not only that, extant research often theorizes health-promoting leadership as a combination of a series of direct and explicit health-related behaviors, neglecting the potential social information it may convey to employees. Based on social information processing theory, this study empirically examines how and when health-promoting leadership can facilitate employees’ health status. Using a time-lagged data of 370 employees (i.e., matched to 51 leaders), we found that health-promoting leadership has a significant and positive influence on employees’ health status, and healthy climate acts as a linking pin. In addition, work unit structure moderates the relationship between health-promoting leadership and healthy climate. Specifically, compared with mechanic work unite structure, employees rely more on social information conveyed by health-promoting leadership when working at an organic work unite structure. This study not only extends current knowledge about the effect of health-promoting leadership, but also provides useful guidance for practitioners.